GAMBARAN PENGETAHUAN KADER SANTRI TENTANG POSYANDU SANTRI - Zuliani; Ana Farida Ulfa; Masruroh; Pujiani; Siti Muniroh; Abdul Ghofar (Universitas Pesantren Tinggi Darul Ulum, 2022)
Posyandu is a form of community-based health effort that is managed and organized from, by for and with the community in the implementation of health development, in order to empower the community and provide convenience to the community in obtaining basic health services. The purpose of this research is to find out the description of the knowledge of the santri cadres about the posyandu santri. The research method was carried out using descriptive quantitative research methods. categorized into good, sufficient, and poor knowledge. Analysis of the data used is univariate analysis. The results showed that the majority of posyandu santri cadres at Darul Ulum Islamic Boarding School were aged 36–45 years and were female. All cadres work as workers and most posyandu cadres have received training on posyandu with sufficient knowledge. Posyandu cadres must be able to divide working time and posyandu activities. Keywords: Knowledge, Cadres, Posyandu, Students